Analysis of flavor change in the industrial production of fungal fermentation based mussel (Mytilus edulis) cooking liquor using a laser irradiation desorption based GC/MS method. (September 2019) - Song, Gongshuai; Zhang, Mengna; Zhou, Xiaomin; Ma, Yongjun; Shen, Qing
Abstract: The commonly discarded mussel cooking liquor (MCL) of Mytilus edulis is an important resource for industrial preparation of fungus ( Aspergillus oryzae ) fermented condiment. In this study, the fermentation degree of MCL was evaluated by analyzing the changes of volatile flavor using a newly established laser irradiation desorption (LID) method coupling a 450 nm blue semiconductor laser to a headspace solid-phase microextraction gas chromatography mass spectrometry (HS-SPME GC/MS). Under the optimized laser conditions (laser power 10 W, irradiation time 5 min, sample volume 3 g), the effect of fungal fermentation was investigated, and a total of 52 volatile compounds in the fermented MCL were detected, such as furans, aromatic compounds, and sulphur and nitrogen containing compounds. By strictly analyzing the characteristic volatiles, the MCL was well processed and the fermentation product showed a desirable and umami flavor, whereas the fishy and burnt smell was roughly removed. Compared with traditional analytical methods, the proposed LID–HS–SPME analysis showed significant characteristic profile and reduced time to only 5 min. The results indicated that the LID–HS–SPME analysis is reliable, efficient, and suitable for industrially used for monitoring the preparation of fungal fermented MCL. Graphical abstract: Image 1 Highlights: The waste of mussel cooking liquor (MCL) was processed by fungal fermentation. A laser was coupled to HS-SPME GC/MS for monitoring the fermentation degree. The volatile compounds were evaluated during the industrial production of condiment. The proposed strategy showed superiority when compared with traditional methods.